Physical Exercise in Patients with Fabry Disease – a Pilot Study - Schmitz, B.; Thorwesten, L.; Lenders, M.; Duning, T.; Stypmann, J.; Brand, E.; Brand, S.-M. (International Journal of Sports Medicine, 2016)
The aim of this study was to assess the extent of exercise intolerance in Fabry disease (FD) patients and to report individual effects of physical exercise. Exercise capacity and strength of 14 patients (mean age 46 years, 6 females) were determined using cycle ergometry and isokinetic measurements. Patients performed a strength/circuit exercise training protocol for 12 months. The mean relative maximum performance of the group was low at baseline and increased by 12.1% (baseline: 1.9 [0.9−3.4] W·kg−1vs. re-test: 2.1 [1.1–3.8] W·kg−1; p=0.035) during the study. Patients’ mean baseline maximum performance blood lactate of 5.4 [1.3–9.9] mmol·L−1 increased to a mean of 7.2 (2.4–10.2) mmol·L−1 (p=0.038). Mean strength of the lower limbs (left/right extensors and flexors, total work of 5 sets) changed from 2269 (1017–2913) kg·m2·s - 2 to 2325 (1359–3107) kg·m2·s-2 (not significant). Patients reported increased well-being, daily activity and reduced fatigue during the study. Our results indicate that exercise intolerance in FD patients often results from physical inactivity. FD patients may perform exercise training to improve exercise capacity and muscle strength. Future studies will address the clinical benefits of exercise in FD.
Keywords: rare disease; lysosome; α-Galactosidase A; globotriaosylceramide